PEMILIHAN ALTERNATIF SIMPLISIA MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) DAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Febrianita Indah Perwitasari; Arief Andy Soebroto; Nurul Hidayat (Journal of Environmental Engineering and Sustainable Technology, 2015)
Nowadays, people tend to consume organic stuff for meal and medication because of its condition of being secure and inexpensive price. Simplisia is organic material which is not yet processed in order to cure the illness. The part that is used from the whole part to the each piece of simplisia, such as leaves, flowers, fruits, and so on. Simplisia has been being used for solution to the illness, especially at Poli Obat Tradisional RSUD Dr. Soetomo. There are many variants of illness that can be cured by simplisia and there are many variants of simplisia than can be used to cure the illness, which are all usually made the people confused which one is the best variant to cure. Regarding of choosing the alternatives, there is more than one method in Decision Support System that can be used to solve the problem. In this research, there will be two methods that aim at finding the best alternative of simplisia, which are Weighted Product (WP) and Simple Additive Weighting (SAW). Comparison research is used to decide which method as the best method on giving simplisia for the illness. The test scenario is comparing between the result which is given by the system and by the doctor. The accuracy of the result for WP method is 89% and SAW method is 89%.